The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1111/jth.12579
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab as first‐line treatment for the management of adult patients with non‐severe hemophilia A and inhibitors

Abstract: patients with non-severe hemophilia A and inhibitors. J Thromb Haemost 2014; 12: 897-901.Summary. Background: The role of immunosuppression in the management of patients with congenital hemophilia and inhibitors is uncertain. The use of rituximab has been limited to case reports and case series. In most reports, rituximab was used as second-line or third-line treatment following failure of conventional immune tolerance induction therapy, and more commonly in pediatric patients. Objectives: The objective of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Nevertheless, in the INSIGHT study (International Study on Etiology of Inhibitors in Patients with a Moderate or Mild Form of Hemophilia A, Influences of Immuno‐Genetic & Hemophilia Treatment Factor), which included 101 non‐severe patients with haemophilia A and inhibitors, inhibitors disappeared in the majority of patients (72/101; 72%), either spontaneously (51/73; 70%), or after eradication treatment (21/28; 75%) . In patients with mild haemophilia A, FVIII inhibitors may share features with FVIII autoantibodies that occur commonly in acquired haemophilia A, and this may explain why immunosuppressive therapy can be effective in reducing the inhibitor titre in some patients …”
Section: Immune Tolerance Inductionmentioning
confidence: 98%
“…Nevertheless, in the INSIGHT study (International Study on Etiology of Inhibitors in Patients with a Moderate or Mild Form of Hemophilia A, Influences of Immuno‐Genetic & Hemophilia Treatment Factor), which included 101 non‐severe patients with haemophilia A and inhibitors, inhibitors disappeared in the majority of patients (72/101; 72%), either spontaneously (51/73; 70%), or after eradication treatment (21/28; 75%) . In patients with mild haemophilia A, FVIII inhibitors may share features with FVIII autoantibodies that occur commonly in acquired haemophilia A, and this may explain why immunosuppressive therapy can be effective in reducing the inhibitor titre in some patients …”
Section: Immune Tolerance Inductionmentioning
confidence: 98%
“…In a systematic review of 49 haemophilia patients with inhibitors, rituximab appeared to be more effective in NSHA patients when administered concomitantly with FVIII concentrates [7]. We reported our single-centre retrospective review of nine consecutive patients with NSHA over a 13-year period; this study demonstrated successful use of singleagent rituximab as first-line therapy for inhibitor eradication with sustained success in seven of the nine patients [6].…”
mentioning
confidence: 86%
“…Immunosuppressive (IS) drugs, such as corticosteroids and rituximab, either alone or in combination with ITI, have also been used for inhibitor eradication, with inconsistent success rates [4,6,7]. We reported our single-centre retrospective review of nine consecutive patients with NSHA over a 13-year period; this study demonstrated successful use of singleagent rituximab as first-line therapy for inhibitor eradication with sustained success in seven of the nine patients [6]. We reported our single-centre retrospective review of nine consecutive patients with NSHA over a 13-year period; this study demonstrated successful use of singleagent rituximab as first-line therapy for inhibitor eradication with sustained success in seven of the nine patients [6].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, limited data are available on this regimen in non‐severe haemophilia patients, and this approach appears to be less effective than in patients with severe haemophilia (Kempton et al , ). Immunosuppressive drugs, such as corticosteroids and rituximab, either alone or in combination with immune tolerance introduction, have also been used for inhibitor eradication, but with inconsistent success rates (Kempton et al , ; Lim et al , ). Due to the antibodies neutralising FVIII concentrates, by‐passing agents, such as activated recombinant FVII or activated prothrombin complex concentrates are potential alternatives (Matino et al , ).…”
mentioning
confidence: 99%